Characterization of exosomes in peritoneal fluid of endometriosis patients - Nazri, HM; Imran, M; Fischer, R; Heilig, R; Manek, S; Dragovic, RA; Kessler, BM; Zondervan, KT; Tapmeier, TT; Becker, CM (Elsevier, 2020)
Objective: To demonstrate the feasibility of studying exosomes directly from peritoneal fluid, we isolated exosomes from endometriosis patient samples and from controls, and characterized their cargo. Design: Case-control experimental study. Setting: Academic clinical center. Patient (s): Women with and without endometriosis who underwent laparoscopic surgery (n ¼ 28 in total). Intervention (s): None. Main Outcome Measure (s): Concentration of exosomes within peritoneal fluid and protein content of the isolated exosomes. Result (s): Peritoneal fluid samples were pooled according to the cycle phase and disease stage to form six experimental groups, from which the exosomes were isolated. Exosomes were successfully isolated from peritoneal fluid in all the study groups. The concentration varied with cycle phase and disease stage. Proteomic analysis showed specific proteins in the exosomes derived from endometriosis patients that were absent in the controls. Five proteins were found exclusively in the endometriosis groups: PRDX1, H2A type 2-C, ANXA2, ITIH4, and the tubulin a-chain. Conclusion (s): Exosomes are present in peritoneal fluid. The characterization of endometriosis-specific exosomes opens up new avenues for the diagnosis and investigation of endometriosis